The Influence of Environmental, Social, Governance (ESG) and Company Size on Stock Returns (Case Study of Mining Sector Companies Listed on the IDX 2016-2023 Period) - Karnaen, Dilfah Fadiah Dzul; Maryani, Neni (CV. Proaksara Global Transeduka, 2025)
The variability in stock performance within the Indonesian mining industry provides a stimulus to investigate the determining factors, such as the disclosure of Environmental, Social, and Governance (ESG) information and the size of the company. The main aim of this study is to evaluate the influence of ESG factors and company size on the performance of stocks. The research adopts a quantitative approach with a focus on description. Information is collected from the annual and sustainability reports of specific companies. Purposive sampling method was employed to choose 7 companies in the mining industry that are listed on the Indonesia Stock Exchange from 2016 to 2023, resulting in a total of 52 data points. The outcomes of the regression analysis revealed that individual ESG factors and the size of the company did not have a significant impact on stock returns. Moreover, when taken into account collectively, ESG factors and company size also did not show any significant influence on stock returns. This investigation suggests that investors in the mining sector do not give much importance to these aspects while making investment choices.